Find h (x) + g (x) h (x) = x2 + 6x and g (x) = -2x - 3 A. x2 - 4x - 3 B. x2 + 8x - 3 C. x2 + 4x - 3 D. x3 + 4x2 - 3
1 answer:
Answer:
Step-by-step explanation:
x^2 + 6x - 2x - 3
x^2 + 4x - 3
answer is C
You might be interested in
Answer:
what are your answer choices?
Step-by-step explanation:
Answer:
Step-by-step explanation:
as
I=PRT
SO
T=I/PR
Answer: no
Step-by-step explanation: because it’s equal
Answer:
1 fact per 3 seconds because you divide 300 by 100
Answer:
2
Step-by-step explanation:
• + • = ••
1 + 1 = 2